2011
DOI: 10.1167/11.6.6
|View full text |Cite
|
Sign up to set email alerts
|

Temporal course of position shift for a peripheral target

Abstract: When a target is presented near a leading cue stimulus, the perceived location of the target is displaced from the cue (attentional repulsion). On the other hand, a memorized target is sometimes mislocalized toward the cue (attentional attraction). The present study aimed at clarifying the temporal relationship between attentional repulsion and attentional attraction. We used a relative judgment task wherein observers judged whether the horizontal location of the target circle was displaced leftward or rightwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…Although some studies using static stimuli show that a salient stimulus repels the perceived position of a subsequent target (Suzuki & Cavanagh, 1997;DiGiacomo, & Pratt, 2012) others instead report attraction (Zimmermann, Fink, & Cavanagh, 2013;Yamada, Kawabe, & Miura, 2008). Yamada et al (2011) showed that observers mislocalized a target closer to a salient inducer that preceded it. These authors suggested that the attraction was caused by the averaging of the memorized locations of the target and the precue.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies using static stimuli show that a salient stimulus repels the perceived position of a subsequent target (Suzuki & Cavanagh, 1997;DiGiacomo, & Pratt, 2012) others instead report attraction (Zimmermann, Fink, & Cavanagh, 2013;Yamada, Kawabe, & Miura, 2008). Yamada et al (2011) showed that observers mislocalized a target closer to a salient inducer that preceded it. These authors suggested that the attraction was caused by the averaging of the memorized locations of the target and the precue.…”
Section: Discussionmentioning
confidence: 99%
“…The localization of a target has been investigated by using a relative localization task in which the target location was subjectively compared with the location of a simultaneously presented or a delayed probe. The mislocalization of a target, away from a pre-cued location, occurred when the target and probe were simultaneously presented (Suzuki & Cavanagh, 1997;Yamada et al, 2011). On the other hand, the mislocalization of a target toward a pre-cued location occurred when the target preceded the probe by approximately 1 sec (Yamada et al, 2008b(Yamada et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…This type of mislocalization occurs because the neural sensitivity of position coding units is inhibited around a focus of attention, and this inhibition resultantly shifts the spatial centroids of population activities of the unit, coding a target location away from the pre-cued location (Suzuki & Cavanagh, 1997). On the other hand, a memorized location of a target is reproduced with a bias toward a pre-cued location (Yamada, Kawabe, & Miura, 2008b, 2012Yamada, Miura, & Kawabe, 2011). The researchers suggest that the spatial distribution of attention modulates location signals of the target around the pre-cued location, and this leads to the mislocalization of the target toward the pre-cued location (Yamada et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations